[OP.8E.07] MIDDLE-TERM DIETARY SUPPLEMENTATION WITH RED YEAST RICE PLUS COENZYME Q10 IMPROVES LIPID PATTERN, ENDOTHELIAL REACTIVITY AND ARTERIAL STIFFNESS IN MODERATELY HYPERCHOLESTEROLEMICS. (September 2016) - Cicero, A.F.G.; Morbini, M.; Rosticci, M.; D'addato, S.; Grandi, E.; Borghi, C.
Abstract : Objective: Red yeast rice is a well-known lipid-lowering nutraceutical. The aim of this double-blind, randomized, placebo-controlled, clinical trial was to investigate if the known benefits on lipid pattern of a 6-month treatment with 10 mg monacolins could be also associated to changes in endothelial function and arterial stiffness. Design and method: This double blind, placebo-controlled, randomized clinical trial was carried out on 40 moderately hypercholesterolemic subjects, non smokers, pharmacologically untreated, in primary prevention for cardiovascular diseases (Clinicaltrial.gov ID NCT02492464). After 4 weeks of diet and physical activity, patients were allocated to treatment with an indistinguishable pill of placebo or with an active product containing 10 mg monacolins from Monascus purpureus and 50 mg coenzyme Q10 to be assumed for 6 months. Endothelial reactivity and arterial stiffness have been measured through the validated Vicorder® device. Results: When compared to the placebo phase, during monacolin treatment patients experienced a more favorable percentage change in LDL-cholesterol (LDL after monacolin treatment: −27.7%; LDL after placebo treatment: +5.0%, p < 0.05). As it regards the vascular parameters, endothelial reactivity (pulse volume displacement after monacolin treatment: +6.0%; pulse volume displacement after placebo treatment: +0.5%, p < 0.05), and arterial stiffness (pulse wave velocity after monacolin treatment: −0.4%; pulse wave velocity after placebo: +0.1%, p < 0.05) also significantly improved after monacolin treatment only. Conclusions: Based on our data, the long-term assumption of a red yeast rice dietary supplement containing 10 mg monakolins per daily dose seems to be associated to an improvement of LDL-cholesterolemia, endothelial reactivity and pulse wave velocity in moderately hypercholesterolemic subjects